Spontaneous pneumomediastinum, pneumothorax and subcutaneous emphysema in COVID-19: case report and literature review - Shan , Shi (2020)
Coronavirus Disease 2019 (COVID-19) has rapidly spread worldwide. Numerous studies have shown its typical and atypical CT findings. We report one COVID-19 patient who presented with a transient pneumothorax, spontaneous pneumomediastinum (SP), as well as subcutaneous emphysema during hospitalization. Chest CT andclinical findings were discussed, and a literature review is presented. The probable cause of SP in COVID-19 was alveolar damage. Once pneumothorax and SP were present, the patient should be carefully monitored to prevent respiratory deterioration, especially when lung lesions are severe.